Cardiovascular disease management through restrained inflammatory responses - R. Jabir, Nasimudeen; Tabrez, Shams (Current Pharmaceutical Design, 2016)
Cardio vascular disease (CVD) is the end result of the accumulation of atheromatous plaques within the walls of the coronary arteries and remains the leading cause of death worldwide. Vascular inflammation and associated ongoing inflammatory responses have been considered as the critical culprits in the pathogenesis of CVD. Moreover, the activation of inflammatory pathways is not confined to coronary lesions only but involves the activation of neutrophils, monocytes and lymphocytes in peripheral blood. In view of high mortality rate associated with this devastated disease, it is essential that CVD and related complications should be taken care off at its earliest. To achieve that goal, some inflammatory mediators could be potentially targeted. In the current article, we will highlight targeting some inflammatory mediators viz. IL-1, IL-6, TNF-α etc for CVD management. As far as our knowledge goes, we are for the first time reporting the targeting inflammatory mediators especially IL-1, IL-6 and TNF-α together in a single article. Based on our review, we believe that scientific community will come up with certain anti-inflammatory agents against atherosclerosis in near future and hopefully that will be used for the successful management of CVD patients.
Keywords: Cardiovascular disease